Molecular characterization of potato virus Y resistance in potato (Solanum tuberosum L.) - Bhardwaj, Vinay; Sharma, Reena; Dalamu, Dalamu; Srivastava, A.K.; Bhardwaj, R.; Singh, Rajendra; Singh, B.P. (The Indian Journal of Genetics and Plant Breeding, 2016)
Amongst viruses, Potato virusY (PVY) is the most prevalent virus affecting potato productivity. Resistance genes (Ry) in Solanum tuberosum subsp. andigena (Ryadg) and Solanum stoloniferum (Rysto) confer extreme resistance (ER) to PVY. SCAR marker RYSC3 for Ryadg gene and SSR marker STM0003 for Rysto gene were used to screen 119 potato genotypes including 44 Indian varieties. These genotypes were also challenge inoculated with PVYo strain and confirmed for ER by DAS-ELISA. Gene Ryadg was present in 11 and Rysto in 22 genotypes, while 3 genotypes possessed both the genes. The statistical analysis indicated that among the two tested markers, RYSC3 is better diagnostic of PVY resistance. The identified genotypes can serve as potential source for future virus resistance breeding programs.